Moderate prenatal alcohol exposure suppresses the TLR4-mediated innate immune response in the hippocampus of young rats. (23rd April 2019) - Wang, Peng; Liu, Bo-Ya; Wu, Ming-Mei; Wei, Xiao-Yan; Sheng, Sen; You, Si-Wei; Shang, Li-Xin; Kuang, Fang
Highlights: Moderate prenatal alcohol exposure (PAE) itself induced a long term up-regulation of TLR4-mediated inflammatory response in the hippocampus of young rats. Moderate PAE led to suppressed innate immune reaction to direct LPS challenge in the hippocampus of young rats. PAE following LPS administration significantly down regulated MyD88-independent pathway of TLR4 response. Abstract: Prenatal alcohol exposure (PAE) could lead to developmental disorders of the central nervous system (CNS) and mental retardation. Toll-like receptor (TLR) 4 plays an important role in PAE-induced neurodevelopmental defects. However, how PAE affects TLR4 response in the brain remains controversial. Using a moderate PAE model by feeding pregnant rats with liquid ethanol diet, we investigated the TLR4-mediated response to intraventricular injection of lipopolysaccharide (LPS) in the hippocampus of PEA rats at postnatal day (PND) 30. The results showed that PAE significantly up-regulated the expression of Toll-Interleukin-1 Receptor (TIR)-domain-containing adaptor protein inducing interferon (IFN)-β (TRIF), TNF-α, and IL-1β in the rat hippocampus in the absence of LPS, indicated by western blot assay. LPS treatment dramatically up-regulated the expressions of TLR4 and its downstream molecules in the hippocampus of paired-food and control groups. But no such significant changes of those molecules were found in the hippocampus of PAE animals. Moreover, the LPS stimulation even down-regulated the levels of TLR4 and TRIF in the PAE group. These data suggest that the relatively moderate level of PAE may lead to a mild neuroinflammation and a suppression of TLR4-mediated response to LPS in the hippocampus of young rats. As innate immunity plays crucial roles in CNS development, moderate PAE-induced suppression of TLR4-mediated response may serve as a new candidate mechanism of CNS developmental defects.